EFEKTIVITAS KETERSEDIAAN HANDRUB TERHADAP KEPATUHAN PERAWAT DALAM HAND HYGIENE DI RUANG HARDJA 1A RS BHAYANGKARA TINGKAT I RADEN SAID SUKANTO JAKARTA - Hemi Afifah (2022)
Nurse compliance is a nurse's behavior and attitude in obeying the standards and rules that exist in the nursing room. Nurses in carrying out nursing actions must begin with hand hygiene, and this must be adhered to because it is a preventive measure and infection control. The purpose of this study was to determine the compliance of nurses in carrying out hand hygiene using handrubs. The number of respondents was 10 nurses, carried out using descriptive analysis with the observation method on nurses during hand hygiene using handrubs. The result of compliance before providing a handrub of 10%, and after providing a handrub in each patient bed amounted to 80%. It was concluded that there was an increase in nurse compliance before it was provided and after handrubs were provided in each patient's bed, and there were nurse complaints about the limitations of the handrubs available in the room. Recommendations that the results of the study be used as an evidence-based to submit a budget regarding the availability of handrubs in the room. Keywords : Compliance, Hand hygiene, Handrub, Nurse.